Development of a Swirl‐Induced Rotating Glow Discharge Reactor for CO2 Conversion: Fluid Dynamics and Discharge Dynamics Studies. Issue 12 (3rd December 2020) - Raja, Bharathi; Sarathi, Ramanujam; Vinu, Ravikrishnan
Abstract : A novel concept of swirl flow–induced rotating glow discharge for converting carbon dioxide from industrial flue gas to valuable carbon monoxide and oxygen is developed. Maximum energy efficiency of 64 % is recorded in the turbulent flow regime due to the formation of central toroidal recirculation zones. More details can be found in article number 2000535 by Bharathi Raja, Ramanujam Sarathi, and Ravikrishnan Vinu.